A Study to Determine The Antecedents of The Prosocial Rule Breaking Behaviour: A Qualitative Practice for Hotel Businesses - Merve Gözde Durmaz; Gülten Gümüştekin (Istanbul Management Journal)
Prosocial behaviours are considered as pro-social behaviours that contribute to social welfare, benevolent, and do not consider individual interests. Prosocial behaviours are basically shaped by the motive of providing benefit and helping the society. While the employees exhibiting these behaviours in the social sense engage in pro-social behaviours, the social and institutional benefitoriented mindset can sometimes result in behaviours that can bend the rules of the institutions. For this purpose, nine 4 and 5 star hotels operating in the city centre of Bursa were included in the study. Data were collected by conducting face-to-face interviews with 37 hotel employees with at least two years of experience working in different departments. The data obtained from the interviews were coded, categorized and interpreted using the MAXQDA qualitative data analysis program. According to the results of the qualitative analysis, it was determined that the hotel employees expressed the prosocial rule breaking behaviour intensively behaviour required by the industry, customer orientation, benefiting the business, etc.). However, the antecedents of the prosocial rule breaking behaviours of the employees were classified under 3 main themes as individual, organizational and environmental. According to the results of our study, it can be stated that there is no sense of personal interest behind the prosocial behaviour of hotel employees, and the basis of this behaviour is reinforced by customer-oriented and organizational-oriented benefits and/or benevolence feelings.